2012
DOI: 10.1080/15456870.2012.637027
|View full text |Cite
|
Sign up to set email alerts
|

Information Seeking About Global Climate Change Among Adolescents: The Role of Risk Perceptions, Efficacy Beliefs, and Parental Influences

Abstract: Global climate change is likely to have significant impacts on public health. Effective communication is critical to informing public decision making and behavior to mitigate climate change. An effective method of audience segmentation, the risk perception attitude (RPA) framework has been previously tested with other health behaviors and classifies people into 4 groups on the basis of their perceptions of risk and beliefs about personal efficacy. The 4 groups – indifference (low risk, weak efficacy), proactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 73 publications
2
96
0
1
Order By: Relevance
“…First, the link between the respondents' trust in science, their personal effort to create an opinion about CC, and their awareness of CC was examined to provide a basic insight for the differentiation that followed. Next, the influence of post-materialism -people prioritizing non-material goods in their lives, particularly individual values such as autonomy and selfexpression, as defined by Inglehart (1995) -was discussed, employing the arguments of Řeháková (2004) and Mead (2012), and the awareness of CC concerns was tested. As our first hypothesis, we assumed that trust in academic sources and the effort to create one's own opinion correlate positively with awareness.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…First, the link between the respondents' trust in science, their personal effort to create an opinion about CC, and their awareness of CC was examined to provide a basic insight for the differentiation that followed. Next, the influence of post-materialism -people prioritizing non-material goods in their lives, particularly individual values such as autonomy and selfexpression, as defined by Inglehart (1995) -was discussed, employing the arguments of Řeháková (2004) and Mead (2012), and the awareness of CC concerns was tested. As our first hypothesis, we assumed that trust in academic sources and the effort to create one's own opinion correlate positively with awareness.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…We used middle school subjects in our case study since middle school students are developmentally able to grasp complex issues such as climate change [23], seem less susceptible to worldview-driven biases around climate change [9], but are influenced by socio-cultural factors such as gender and ethnicity [9], parents, peers, and teachers [21,24,25]. Additionally, we focused on coastal North Carolina counties for our study since people in coastal areas are more apt to perceive threats of climate change since they will likely be most directly affected by climate change impacts such as sea level rise and loss of coastline [26].…”
Section: Introductionmentioning
confidence: 99%
“…More teens than adults understand that global warming is caused mostly by human activities and that carbon dioxide traps heat from the Earth's surface, but nevertheless fewer teens than adults earn a passing (A, B, or C) grade overall (25 % of teens versus 46 % of adults) (Leiserowitz et al 2011). Similarly, another nationally representative survey reported that youth hold weaker intentions to perform climate-friendly behaviors and take fewer climate-friendly actions than their parents (Mead et al 2012). …”
mentioning
confidence: 99%